Low-Latency Wireless LAN Relay Method for Motor System Control in a Robot Arm Frame - Tsuyoshi Kogawa; Toshihisa Nabetani; Tomoya Tandai (IEEE Access)
Various robot arms have been introduced in factories, and their control is facilitated by numerous cables, which can have drawbacks such as limiting the arm’s range of motion. Therefore, wireless control of motors is desirable. This study proposed a wireless relay method for controlling all motors with low latency, even in an environment with poor propagation. Packet error rates (PERs) of wireless communication between a central controller outside a robot arm frame and a wireless module inside the robot arm frame were evaluated, revealing that some angles of the robot arm frame resulted in markedly higher PERs. When each motor is controlled via its own wireless module, all the wireless modules must communicate with a central controller having low latency. To resolve this problem, some wireless modules relay control signals to the poorest-performing wireless module while others relay the state signals of the poorest-performing wireless module to the central controller. State signals include the encoder value of the motor. Low-latency relay is achieved by regulating the timing of transmission for each wireless module. This paper assumes that the central controller must control the robot arm in a closed loop with a response time within a control cycle of 10 ms. When using the proposed method for six axes with wireless LAN, the response time was less than 10 ms. Furthermore, the proposed method reduced the maximum value of the overshoot by a factor of around 15 compared with the method without using any relay.